Analisis Human Error pada Proses Benang Open End di PT. Lotus Indah Textile Industries - Rita Nurul Andita Putri; Anita Oktaviana Trisna Devi; Yunita Primasanti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
PT. Lotus Indah Textile Industries, a manufacturing company in the open-end yarn spinning sector, faces significant issues related to defective products in its production process. This study aims to identify the level of human error among open-end machine operators and analyze the root causes of these errors. The methods employed include the Human Error Assessment and Reduction Technique (HEART) to calculate the Human Error Probability (HEP), as well as Root Cause Analysis (RCA) with the 5 Whys approach to identify the root problems. Data were collected through observation, interviews, and questionnaires during the period of May to June 2025. The results indicate that the activity of